Who Funds Re/integration? Ensuring sustainable services for trafficking victims - Surtees, Rebecca; de Kerchove, Fabrice (Anti-Trafficking Review, 2014)
This article discusses the critical importance of re/integration services in the lives of trafficked persons and as central to an effective anti-trafficking response. It outlines how support and resources for re/integration services have so far not been widely available and the impact of this on trafficked persons. The article also discusses different strategies used within one re/integration initiative—the Trafficking Victims Re/integration Programme (TVRP)—to promote sustainable re/integration services given the limited (and now declining) funding for re/integration in the Balkans. These strategies, which have met varying degrees of success, include: (1) advocating for government funding; (2) leveraging private-sector funding and contributions; and (3) establishing social enterprises to fund re/integration services. The article concludes by advocating greater attention to re/integration services for trafficked persons, including working creatively and collaboratively with civil society, government, the private sector and donors, to ensure that re/integration services are conceptualised, implemented and funded in ways that are sustainable and, thus, offer critical support to trafficked persons. ¿Quién financia la re/integración? Asegurando servicios sostenibles para las víctimas de trata Resumen Este artículo estudia la importancia de los servicios de re/integración en las vidas de las personas objeto de la trata como un aspecto central en la respuesta efectiva a este fenómeno. Se parte de la idea de que los recursos y la asistencia en los servicios de re/integración no han estado abiertamente disponibles y cómo este hecho ha afectado a las víctimas. El texto también expone diferentes estrategias que se han utilizado en una iniciativa de re/integración -el Programa de Re/integración de Víctimas de Trata (TVRP por sus siglas en inglés)- para promover la sostenibilidad de los servicios de re/integración, teniendo en cuenta la limitada (y ahora en descenso) financiación para la re/integración en los Balcanes. Estas estrategias, que han incluido diversos niveles de éxito, incluyen: 1) abogar por la financiación gubernamental; 2) potenciar la contribución y financiación por parte del sector privado; y 3) establecer empresas sociales para financiar los servicios de re/integración. El artículo concluye defendiendo una mayor atención a los servicios de re/integración para las personas objeto de la trata, incluyendo propuestas de trabajo creativas y en colaboración con la sociedad civil, gobiernos, sector privado y donantes, para asegurar que los servicios de re/integración sean conceptualizados, implementados y financiados de forma sostenible y, por tanto, sean capaces de ofrecer una asistencia imprescindible a las personas objeto de la trata.